Cerebral infarction following a carotid Doppler ultrasound: a chance association?. (14th August 2012) - Roberton, Andrew; Shinton, Roger; Clow, Laura; Tudway, David
Abstract : The authors present a case report of a 64-year-old lady with multiple risk factors for atherosclerosis, who suffered an ischaemic stroke immediately following carotid Doppler ultrasound despite therapeutic warfarin and antiplatelet therapy. This event was only 16 days after the patient suffered a first ischaemic stroke during diagnostic coronary angiography following a syncopal episode accompanied with a raised troponin-T. The temporal relationship between the carotid Doppler ultrasound and second ischaemic stroke raised the question whether it was possible that the investigation had caused the stroke, a complication not previously recognised.